PENGARUH DISIPLIN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN PRODUKTIVITAS PEGAWAI PDAM TIRTA INDRAGIRI TEMBILAHAN - Nalapraya, Tresna; Zulfadil, Zulfadil; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the influence of discipline and organizationalculture on employee job satisfaction and Employee Productivity.The population of this research are employee of PDAM Tirta Indragiri, both in theoffice and in the field. The total number of Tirta Indragiri PDAM employees is 174people. The results of the study and discussion are presented using WarpPLS analysis.The result of research was that work discipline had an effect on the employee jobsatisfaction. Organizational culture partially effect on employee job satisfaction. Workdiscipline partially has a significant effect on employee productivity. Organizationalculture partially has a significant effect on employee productivity. Job satisfactionpartialy has a significant effect on employee productivity. If there is an increase in jobsatisfaction, then the productivity of personnel will increase and vice versa, if there is adecrease, then the productivity will decrease as well.